IL-17A Mediates Demyelination by Activating A1 Astrocytes via SOCS3 During Angiostrongylus cantonensis Infection - Zhou, Zongpu; Lin, Tuo; Liu, Zhen; Ding, Qian; Ma, Zhixuan; Li, Wanqi; Xie, Fukang; Lan, Yue; Feng, Ying (Frontiers in Immunology, 2022)
Background Demyelinating disease of the central nervous system is one of the most common neurological diseases and effective treatment is still under in-depth research. Our previous study showed that Angiostrongylus cantonensis infection can induce demyelination injury in mouse brains and IL-17A expression was shown to be significantly increased during this process. Moreover, we found that IL-17A inhibition attenuated the demyelination caused by A. cantonensis infection. However, the underlying mechanisms have not yet been fully elucidated. Methods IL-17A neutralizing antibodies were injected into A. cantonensis infected mice to decrease IL-17A levels. The activation of glial cells in the brain and the expression of cell markers were detected by a variety of methods, including real-time quantitative PCR, western blotting, and immunofluorescence staining. The relationship between IL-17A and astrocyte activation was further identified by in vitro experiments. The role of SOCS3 in the IL-17A stimulating process was determined using RNA-seq data collection of infected mice and the siRNA interference method. Results Demyelination of the corpus callosum was relieved after administration of IL-17A neutralizing antibody and this was accompanied by decreased activation of A1 type astrocytes around this region. The expression of SOCS3 was attenuated and activation of astrocytes by IL-17A was mediated by the IL-17RA/STAT3/SOCS3 pathway. IL-17A not only directly damaged oligodendrocytes but also indirectly damaged oligodendrocytes through A1 astrocyte mediation. Specific siRNA inhibition of IL-17A-inducible SOCS3 in astrocytes alleviated their damaging effects on oligodendrocytes. Conclusion IL-17A plays an important role in demyelination induced by A. cantonensis infection via the IL-17RA/STAT3/SOCS3 pathway in A1-type astrocytes, indicating that specific blockage of IL-17A and SOCS3 activity could be a therapeutic strategy for neuroinflammatory demyelinating diseases associated with astrocyte activation.